Kegiatan Perdagangan: Suatu Penjelasan Berdasarkan Teori Simbolis - Widya Nayati (Berkala Arkeologi, 1995)
Trade is a system composed of various components related to one another. This system is very flexible in scope, both time and area coverage. One another can be seen by each component but it will be clearer when viewed globally. This specificity is what makes the trading system have similarities and differences between one area and another, with varying times. This is because it is influenced by various factors, from outside as well as from within the system itself. The differences that exist arise, among others, due to the existence of political-economic-religious activities which ultimately affect the changes in human supporters. A summary of the archaeological-historical data will be used in analyzing trading activities in Indonesia from past to present.